234k views
3 votes
Why does multiplying a + bi by the complex conjugate a -bi eliminate I from the expression

User Fvukovic
by
5.6k points

1 Answer

3 votes

Step-by-step explanation

The reason is that


i^2=-1


If we multiply
a+bi by its conjugate
a-bi


We obtain;



(a+bi)(a-bi)

This is difference of two squares so we obtain;



(a+bi)(a-bi)=a^2-(bi)^2


This further gives us,


(a+bi)(a-bi)=a^2-b^2i^2

Since the
i^2=-1, we substite to get;


(a+bi)(a-bi)=a^2-b^2(-1)

The
i is now eliminated and we get,



(a+bi)(a-bi)=a^2+b^2






User Dolkar
by
5.8k points